1996
DOI: 10.1042/bj3180609
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-induced tyrosine dephosphorylation of paxillin and focal adhesion kinase requires active phosphotyrosine phosphatase 1D

Abstract: Insulin stimulation of fibroblasts rapidly induces the tyrosine dephosphorylation of proteins of 68 kDa and 125 kDa, in addition to the tyrosine phosphorylation of the insulin receptor beta-chain, insulin receptor substrates 1 and 2, and Shc. Using specific antibodies, the 68 kDa and 125 kDa proteins were identified as paxillin and focal adhesion kinase (pp125FAK) respectively. We have examined whether dephosphorylation of paxillin and pp125FAK requires interaction of the cells with the extracellular matrix. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 67 publications
6
39
1
Order By: Relevance
“…Under the experimental conditions used in this study (cells were plated in complete medium) p125FAK was not tyrosine phosphorylated in response to cell-substrate interaction ( Figure 1a, lanes 9 ± 12). Previous studies have reported that serum components, especially insulin and insulin-like growth factors, stimulate the tyrosine dephosphorylation of p125FAK (Konstantopoulos and Clark, 1996;Ouwens et al, 1996;Pillay et al, 1995;Tobe et al, 1996). Thus, it is possible that tyrosine phosphorylation of p125FAK was not evident when cells were plated in serum-containing media due to the opposing in¯uences of serum growth factors such as insulin and IGF-1 (that promote dephosphorylation of focal adhesion proteins) and integrin engagement (that promote the tyrosine phosphorylation of focal adhesion proteins).…”
Section: Resultsmentioning
confidence: 99%
“…Under the experimental conditions used in this study (cells were plated in complete medium) p125FAK was not tyrosine phosphorylated in response to cell-substrate interaction ( Figure 1a, lanes 9 ± 12). Previous studies have reported that serum components, especially insulin and insulin-like growth factors, stimulate the tyrosine dephosphorylation of p125FAK (Konstantopoulos and Clark, 1996;Ouwens et al, 1996;Pillay et al, 1995;Tobe et al, 1996). Thus, it is possible that tyrosine phosphorylation of p125FAK was not evident when cells were plated in serum-containing media due to the opposing in¯uences of serum growth factors such as insulin and IGF-1 (that promote dephosphorylation of focal adhesion proteins) and integrin engagement (that promote the tyrosine phosphorylation of focal adhesion proteins).…”
Section: Resultsmentioning
confidence: 99%
“…We now propose that PTPs are targets for the ECM signals that regulate differentiation in mammary cells, possibly through direct interaction with proteins within adhesion complexes (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…In one study, insulininduced tyrosine dephosphorylation of FAK and paxillin was found to be mediated by protein phosphatase SHP2 (Ref. 53; but see also Ref. 17); SHP2 is also a known component of the EGF receptor signaling pathway (38).…”
Section: Discussionmentioning
confidence: 99%